Pathogenic Role and Antibiotic Resistance of Methicillin-Resistant Staphylococcus aureus (MRSA) Strains Causing Severe Community-Acquired Pneumonia in Vietnamese Children - Khai Quang Tran; Thuy Thi Dieu Nguyen; Van Hung Pham; Quan Minh Pham; Hung Do Tran (Advances in Respiratory Medicine, 2023)
In recent years, the pathogenic role and antibiotic resistance of methicillin-resistant Staphylococcus aureus (MRSA) strains causing severe community-acquired pneumonia (CAP) have received increasing attention in clinical practice. The aim of this study was to determine the rate of isolates of MRSA strains causing severe CAP in children and to assess their level of antibiotic resistance. The study design was cross-sectional. Children with severe CAP were sampled by nasopharyngeal aspiration for the culture, isolation, and identification of MRSA. Antimicrobial susceptibility testing was performed using the gradient diffusion method to determine the minimum inhibitory concentration (MIC) of antibiotics. Results: MRSA was identified as the second leading cause of severe CAP in Vietnamese children. The rate of isolates of S. aureus was 41/239 (17.5%), of which most were MRSA, at 32/41 (78.0%). MRSA strains were completely non-susceptible to penicillin (100%), more resistant to clindamycin and erythromycin, less sensitive to ciprofloxacin and levofloxacin, and fully susceptible to vancomycin and linezolid, with a 32-fold decreased MIC90 for vancomycin (0.5 mg/L) and a 2-fold decreased MIC90 for linezolid (4 mg/L). Therefore, vancomycin and linezolid may be appropriate options for severe CAP identified by MRSA.